Preclinical safety evaluation of human platelets treated with antimicrobial peptides in severe combined immunodeficient mice. Issue 3 (30th June 2013) - Bosch‐Marcé, Marta; Mohan, Ketha V.K.; Gelderman, Monique P.; Ryan, Patricia L.; Russek‐Cohen, Estelle; Atreya, Chintamani D.
<x xml:space="preserve">Abstract</x> Background Bacterial sepsis is a complication attributed to room temperature (RT)‐stored platelets (PLTs) in transfusion medicine. Antimicrobial peptides (AMPs) are emerging as new therapeutic agents against microbes. We had previously demonstrated bactericidal activity of select synthetic AMPs against six types of bacteria in stored PLTs. In this report, we tested these AMPs for their potential antibody response and interference with the recovery and survival of human PLTs in an animal model. Study Design and Methods Two separate studies were conducted to evaluate the safety of the synthetic AMPs. 1) Two AMPs (PD3 and PD4), derived from thrombin‐induced human PLT microbicidal protein, and four repeats of arginine‐tryptophan (RW), containing two to five repeats (RW2‐RW5), were tested in rabbits for potential antibody response. 2) RT‐stored human PLTs treated for 2 hours with each of the six AMPs individually or with phosphate‐buffered saline (PBS) alone were infused into severe combined immunodeficient (SCID) mice to evaluate their in vivo recovery and survival by flow cytometry. Results Except for PD3, which showed a weak immune response, all other peptides did not induce any detectable antibodies in rabbits. Furthermore, all six AMPs tested did not significantly affect the in vivo recovery and survival of human PLTs in SCID mice compared to PBS alone–treated PLTs. Conclusion Preclinical evaluation studies reported here demonstrate that the selected AMPs used in the study did not adversely affect the human PLT recovery and survival in the SCID mouse model, suggesting further study of AMPs toward addressing the bacterial contamination of PLTs.